Design of Detection Device for Cu Contaminated WaterUsing Induction Principle - Frida Agung Rakhmadi; Astika Rusma Dewi; Ahmad Farid Azizi (Department of Physics, Sebelas Maret University, 2015)
The research on detection device design of Cu contaminated water using induction principle has been done. The purpose of this research is to create a detection device of Cu contaminated water using induction principle, characterize the precision of core sensor on detection device, characterize the stability of detection device, and implement the detection device to Cu contaminated water. This research was conducted in four phases: manufacturing of detection device, characterization of core sensor precision, characterization of detection devices stability, and implementation of detection device to Cu contaminated water. The results showed that the detection device of Cu contaminated water using induction principle has been successfully made. The precision of core sensor was 99.96%, while the stability of detection device was the 60th second after turn-on. The success rate of detection device implementation on Cu contaminated water was 100.00%.